Reconfigurable Two‐Dimensional DNA Lattices: Static and Dynamic Angle Control. Issue 49 (5th November 2021) - Wang, Wen; Chen, Chunyu; Vecchioni, Simon; Zhang, Tianqing; Wu, Chengxian; Ohayon, Yoel P.; Sha, Ruojie; Seeman, Nadrian C.; Wei, Bryan
Abstract: Branched DNA motifs serve as the basic construction elements for all synthetic DNA nanostructures. However, precise control of branching orientation remains a key challenge to further heighten the overall structural order. In this study, we use two strategies to control the branching orientation. The first one is based on immobile Holliday junctions which employ specific nucleotide sequences at the branch points which dictate their orientation. The second strategy is to use angle‐enforcing struts to fix the branching orientation with flexible spacers at the branch points. We have also demonstrated that the branching orientation control can be achieved dynamically, either by canonical Watson–Crick base pairing or non‐canonical nucleobase interactions (e.g., i‐motif and G‐quadruplex). With precise angle control and feedback from the chemical environment, these results will enable novel DNA nanomechanical sensing devices, and precisely‐ordered three‐dimensional architectures. Abstract : Branching orientation control of four‐arm junction lattices can be achieved by branch point sequences or by enforcing struts.